THE EFFECT OF CURCUMINOID TO NOISE EXPOSURE VIEWED FROM THE EXPRESSION OF HEAT SHOCK PROTEIN-70 (HSP-70) IN COCHLEAR FIBROBLASTS OF RATTUS NORVEGICUS: Pharmaceutical Science-Herbal Technology - SITI HAJAR HARYUNA, TENGKU; LUTAN, RAMSI; NYILO PURNAMI; SUPRAPTO MA’AT; WIBI RIAWAN (International Journal of Life Science and Pharma Research, 2013)
Numerous epidemiological and experimental studies have been carried out so far, from which empirical evidences were obtained and various theories were suggested to elucidate a series of Noise-Induced Hearing Loss (NIHL) process at the molecular level. One of them is the increased expression of HSP-70 due to noise exposure. This study was conducted to demonstrate curcuminoid as the safe and effective phytopharmacy in order to prevent the damage of supporting tissues within the cochlear lateral wall which may lead to NIHL viewed from the expression of HSP-70. The samples were 40 Wistar strain white rats (Rattus norvegicus) divided into 8 groups: The control group/K1, Group 2/K2 noise (+) for 2 weeks, Group 3a/K3a noise (+) 50 mg/day curcuminoid (+) for 2 weeks, Group 3b/K3b noise (+) 100 mg/day curcuminoid (+) for 2 weeks, Group 4a/K4a noise (+) 50 mg/day curcuminoid (+) for 2 weeks, untreated for the next 2 weeks, Group 4b/K4b noise (+) 100 mg/day curcuminoid (+) for 2 weeks, untreated for the next 2 weeks, Group 5a/K5a 50 mg/day curcuminoid (+) for 2 weeks, noise (+) and 50 mg/day curcuminoid (+) for the next 2 weeks and Group 5b/K5b 100 mg/day curcuminoid (+) for 2 weeks, noise (+) and 100 mg/day curcuminoid (+) for the next 2 weeks. This study used curcuminoid derived from Curcuma longa L. (Turmeric) with curcuminoid content levels [28.1 ± 1.0]% w/w compared to Standard. All samples were examined for the expressions of HSP-70 in cochlear fibroblasts by Immunohistochemistry method. The data were processed with Analysis of Variance (ANOVA) using the Statistical Analysis System (SAS). The results obtained showed significant differences for the expressions of HSP-70 (p<0.05) in all treatment groups, except in Group 3a and 3b. Curcuminoid proved to be potentially effective in the prevention and treatment for the damage of supporting tissues within the cochlear lateral wall regarding the decreased expression of HSP-70